2019
DOI: 10.1111/odi.13116
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between drugs and burning mouth syndrome? A case–control study

Abstract: Objective The purpose of this case–control study was to compare the pharmacological anamnesis collected from a group of 150 burning mouth syndrome (BMS) patients with that of a control group of 150 patients matched for age and sex. Materials and Methods The patients' medical histories were reviewed, and data on drug therapy were collected. Drugs were classified on the basis of pharmacological effects; the classes were antihypertensives (i.e., ACE inhibitors/ARBs, calcium antagonists, diuretics and beta‐blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Lamey et al (2005) found also significant differences between BMS patients and controls in the use of many medications, with higher use of tranquilizers, hypnotics and self‐medication laxatives by the BMS patients. Azzi et al (2019) found that anxiolytics, but neither antidepressants nor antipsychotics, were linked to the presence of BMS. We have the same results concerning the use of anxiolytics and antipsychotics, but not with respect to the use of antidepressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamey et al (2005) found also significant differences between BMS patients and controls in the use of many medications, with higher use of tranquilizers, hypnotics and self‐medication laxatives by the BMS patients. Azzi et al (2019) found that anxiolytics, but neither antidepressants nor antipsychotics, were linked to the presence of BMS. We have the same results concerning the use of anxiolytics and antipsychotics, but not with respect to the use of antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…BMS, like other persistent pains, is usually accompanied by depression, anxiety (Adamo et al, 2018; Galli, Lodi, Sardella, & Vegni, 2017; IHS, 2018; Jaaskelainen & Woda, 2017; Mitsikostas, Ljubisavljevic, & Deligianni, 2017) and poor sleep quality (Adamo et al, 2018). There are studies that have analysed the possible association between the use of different drugs such as anxiolytics (Azzi et al, 2019) and antihypertensives (Adamo et al, 2019; Azzi et al, 2019) and BMS but have found some controversy. On the other hand, there are studies that have found that BMS patients have low levels of vitamin B1, B2, B6 and B12; folic acid; iron; zinc; mineral deficiencies; and an increase in glucose levels (Acharya, Carlen, Wenneberg, Jontell, & Hagglin, 2018; Lin et al, 2013; Morr Verenzuela, Davis, Bruce, & Torgerson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of primary BMS is poorly understood; however, a complex interplay between neuropathic, immunological, endocrinological, and psychosocial factors has been postulated, and it is found to be more common in women of perimenopausal and postmenopausal age group 2 . Although the etiology for primary BMS remains unclear even today, many local and systemic factors including medications such as angiotensin-converting enzyme inhibitors, angiotensin 2 receptor blockers, and β-blockers have been associated with the secondary BMS 6 . Levenson first described a case of SSRI-induced BMS in a woman aged 56 years who developed glossodynia with fluoxetine, sertraline, and venlafaxine 7 .…”
Section: Discussionmentioning
confidence: 99%
“…These associations of BMS with ACE inhibitors suggested that BMS may be an adverse effect of ACE inhibitors. BMS is an infrequently reported adverse effect of captopril treatment and is even less frequently reported with other ACE inhibitors that act upon the angiotensin-renin system [2,[9][10]. These adverse effects have been reported to be attributed to the chemical structure of the drugs, although this relationship is the matter of some debate [9].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a patient who developed BMS after initiation of angiotensin-converting enzyme (ACE) inhibitors for hypertension whose oral symptoms were eliminated by discontinuing ACE inhibitors and changing to a beta-blocker medication. An association between the onset of a burning sensation in the mouth and the administration of drugs has been known, particularly with antihypertensive or psychotropic medicines [2][3][4][5]. Although BMS is a relatively common intraoral disorder in the dental field, it is rarely recognized by emergency physicians.…”
Section: Introductionmentioning
confidence: 99%